Sistem Pengawasan Profesi Notaris di Indonesia dan Belanda: Studi Komparatif atas Mekanisme Akuntabilitas dan Etika Jabatan - Fahmi Ihsan Margolang; Dewi Mayaningsih (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
This study examines the comparative supervision systems of notarial professions in Indonesia and the Netherlands using a normative and comparative legal approach. In Indonesia, notary supervision is centralized under the Ministry of Law and Human Rights through supervisory councils, yet remains weak in terms of independence and transparency. In contrast, the Netherlands adopts a decentralized and independent model through institutions such as the KNB, the Notarial Disciplinary Board, and the BFT, which ensure accountability and public oversight. The findings reveal that the Dutch system is more effective in enforcing professional ethics and preventing conflicts of interest through mandatory reporting and peer evaluations. The study suggests reforming Indonesia’s supervisory framework by strengthening institutional independence, enhancing the role of professional associations, and ensuring greater transparency. This research aims to contribute to the development of a more accountable and integrity-based notarial supervision system in civil law jurisdictions.